Respuesta :
- Value of x = -2
- Value of y = -1
Putting the values of x and y in equation
[tex] \rm \large \purple\implies \: \:{6x}^{5} \: - \: 3y \: + \: 7 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \rm \large \purple\implies \: \: 6 { (-2)}^{5} \: - \: 3( - 1) \: + \: 7 \\ \\ \rm \large \purple\implies \: \:6( - 32) \: + \: 3 \: + \: 7 \: \: \: \: \: \: \: \: \\ \\ \rm \large \purple\implies \: \: - 192 \: + \: 10 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \rm \large \purple\implies \: \: - 182 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: [/tex]
If x = -2 and y = -1 then 6x⁵ - 3y + 7 = -182
x = -2
y = -1
Solve
6x⁵ - 3y + 7
Let's use substitution method,
What is substitution:
Substitution simply means to put in place of another.
Therefore, let's substitute the values of x and y in the equation.
6x⁵ - 3y + 7
6(-2)⁵ - 3(-1) + 7 = 6(-32) + 3 + 7 = -192 + 10 = -182
learn more on equation here: https://brainly.com/question/26002046?referrer=searchResults